(untitled) (Journal of Hama University, 2024)
Introduction and the aim of the research: Glide path preparation is considered as an essential step in endodontic treatment. Our study aims to evaluate the possibility of preparing narrow root canals with Reciproc Blue files without glide path when using two models of reciprocating motion. Materials and Methods: The research sample consisted of 84 freshly extracted teeth with a single root and canal, which were randomly divided into two equal groups according to the reciprocal movement model used as follows: The first group: Reciproc reciprocating motion model (30 degrees clockwise and 150 degrees counterclockwise( The second group: Wave One reciprocating motion model (35 degrees clockwise and 155 degrees counterclockwise(. The teeth of the sample were prepared with Reciproc Blue 25 gauge files according to the manufacturer’s instructions, and insertion and extraction movements were applied with a capacity not exceeding 3 mm during the automatic reciprocating movement of the file with copious irrigation with sodium hypochlorite. All cases prepared with Reciproc Blue file without glide path were classified as cases in which the file was able to reach the full working length and cases in which the file was not able to reach the full working length, then they were tabulated on the Excel program and success and failure rates were calculated in reaching the full working length , A chi-square test was also performed to study the differences in success or failure frequencies between groups, according to the reciprocal movement model. Reciproc Blue files in narrow root canals whose curvature does not exceed 25 degrees can reach the entire working length without prior preparing of glide path and with high rates. the success rate in reaching the full working length does not follow the reciprocating motion model used.